Maintenance Costs, Obsolescence, and Endogenous Growth - Koen G. Berden; Charles van Marrewijk (Tinbergen Institute, 2001)
We analyze the impact of obsolescence of economic inventions by incorporating maintenance costsin the endogenous growth model of expanding product varieties. This contrasts with the existingliterature, which ignores maintenance costs and uses the model of quality improvements todescribe obsolescence. If the maintenance costs become too high, the operating profits becomenegative and the firm stops producing the variety. This diminishes the life span of innovations,thus reducing the return on investment in research and development and the growth rate of theeconomy.
Keywords: F43; O31; O33; O41; 330; endogenous growth; obsolescence; maintenance; innovation; variety; Instandhaltung; Kosten; Innovation; Lebenszyklus; Neue Wachstumstheorie; Theorie